Implementation of the parent involvement program at TKIT Iqra - Sumayyah, Azelia; Nuraini, Annisa Tri; Septiani, Reni Dwi; Wahyuni, Sri; Pertiwi, Sarah Dian; Fasa, Tresna Maela; Amellyah, Yuly; Mashud, Esya Anesty (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
The family is the first place where the child grows and develops. Parents are people who play an important role in regulating children’s education, both as educators and as people who help children. The involvement of parents in early childhood education has become a hot debate. Most parents spend their time working rather than spending time with their child, according to several surveys and previous research. Ironically, schools also lack programs that can increase parental participation in early childhood programs. This study explores the implementation of the parent involvement program at TKIT IQRA Serang as an effort to support early childhood development. Parental involvement through programs such as home visits, out-of-class learning activities (field trips), and parent associations showed a significant impact on children’s learning motivation, confidence, and social skills. Descriptive research methods with a qualitative approach are used to describe the implementation of the program in depth. The results of the study show that active parental involvement creates a positive synergy between school and family, building a conducive learning environment. However, several challenges were found, including a lack of formal programs and limited resources that affected the sustainability of the program. This study recommends the development of more structured and sustainable programs to increase the effectiveness of parental involvement in early childhood education.